Amateurs without borders : the aspirations and limits of global compassion - Schnable, Allison, 1981- (University of California Press, 2021)
"Amateurs without Borders examines the rise of new actors in the international development world: volunteer-driven grassroots international nongovernmental organizations. These small aid organizations, now ten thousand strong, sidestep the world of professionalized development aid. Instead, NGOs launch projects built around personal relationships and the skills of volunteers. This book draws on fieldwork in the United States and Africa, web data, and IRS records to offer the first large-scale systematic study of these groups. Amateurs without Borders shows the aspirations and limits of personal compassion on a global scale"--